Optical stimulation for restoration of motor function after spinal cord injury - Mallory, Grant W.; Grahn, Peter J.; Hachmann, Jan; Lujan, J. Luis; Lee, Kendall H. (Mayo Clinic proceedings, 2015)
Spinal cord injury can be defined as a loss of communication between the brain and the body due to disrupted pathways within the spinal cord. Although many promising molecular strategies have emerged to reduce secondary injury and promote axonal regrowth, there is still no effective cure, and recovery of function remains limited. Functional electrical stimulation (FES) represents a strategy developed to restore motor function without the need for regenerating severed spinal pathways. Despite its technological success, however, FES has not been widely integrated into the lives of spinal cord injury survivors. In this review, we briefly discuss the limitations of existing FES technologies. Additionally, we discuss how optogenetics, a rapidly evolving technique used primarily to investigate select neuronal populations within the brain, may eventually be used to replace FES as a form of therapy for functional restoration after spinal cord injury.
Gesehen am 05.06.2020